Connecting the unconnected: Lessons for enhancing fast and reliable internet from Southwest Sumba District - Amira Husna; Louis Budiman (Center for Indonesian Policy Studies (CIPS), 2023)
The Indonesian government has prioritized inclusive digital connectivity for the country's economic prosperity. Despite Indonesia's progress toward achieving inclusive digital transformation, the country faces a digital divide across its regions. The ICT Development Index conducted by Statistics Indonesia (2021) shows a stark gap in access and infrastructure, ICT utilization, and ICT proficiency between the western part of Indonesia, specifically Java Island, and the most eastern parts of the country. The ICT development index in eastern regions such as East Nusa Tenggara and Papua is low, with scores ranging from 3.35 to 5.00 out of 10.00 (scores between 2.25-5.00 is categorized as low ICT development) for the years 2020-2021. In contrast, more developed regions - Jakarta and Yogyakarta - scored above 7.00, with Jakarta the only province scoring a high index of above 7.5. Absence of reliable, high-speed internet for the rural poor can exacerbate inequality. Attention to underdeveloped areas must be moved to the forefront of the government's agenda so that inclusive digital transformation can be fully realized.
Keywords: 330; Internet; Telekommunikationsnetz; Infrastrukturversorgung; Indonesien